Blockchain as a Tool to Enhance Economic Development of Tanzania - Likavčanová, Natália; De Castro, Tereza; Valík, Lubomír; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The aim of this thesis is to introduce blockchain technology as a tool of enhancing economic development of countries. The assumption, that technology is a crucial factor is development of countries is based upon the endogenous growth theory. Blockchain is an evolving technology that enables to digitally record and transfer information in a secure and immutable manner with the use of cryptography. This technology can be used in processes in which the transfer of information is traditionally ensured by a third party and in which a fast and accurate information sharing would benefit the whole system. Tanzania, as a developing country, is marked by a fast population growth and its economy is based on agriculture. Despite of the arguably low connection to electric power grid, the majority of the population uses mobile device connection not only for communication but also for inclusion to the formal system, e.g. mobile banking. The institutions in Tanzania is still underdeveloped, which inhibits the further development of the country in its competitiveness, business attraction and human capital evolution. Based on the analysis, two institutions – land registry and healthcare – are identified as sectors in which blockchain could be implemented to support the development of Tanzania. These two institutions and their systems are analyzed and blockchain solutions are introduced. The findings of the thesis suggest that blockchain is an adequate tool structuring the institutional systems in Tanzania, which would positively influence the economic development of the country. This manner of development would not interfere with the natural course of the country’s evolution and would consequently support further the development of human capital in Tanzania.
Vedoucí práce: Tereza De Castro
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses